Pattern of Contraceptive Used by Tribal Couples of Chattogram Hill Tract (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Chattogram hill tract is the least economically developed area of Bangladesh where, education and health care facilities are hard to reach. Pattern of contraceptive use depends on couples’ socio-cultural, education and economic condition.Objective: To find out the pattern of contraceptive used by selected tribal couples of Guimara Upazila of Khagrachari District.Materials and Methods: This descriptive cross-sectional study was conducted from October 2016 to March 2017 on 145 married women age ranging from 15 to 45 years reported to outpatient department of Border Guard Hospital, Guimara, Khagrachari were selected purposively after informed written consent. All the necessary data were collected in a pretested structured questionnaire by face to face interview.Results: Among the 145 respondents highest 50.3% was in age group of 15-25 years. Respondents’ ethnicity was Marma 37.9%, Tripura 38.6% and Chakma 23.5%. Majority 52.4% of the respondents’ profession was farming, 68.3% was illiterate and 55.9% had monthly family income less than five thousand Taka. Only 39.3% respondents were using various types of contraceptives. Among the ethnic groups 47.1 Chakma, 39.3% Tripura and 34.5% Marma respondents were using contraceptives. Among the contraceptive user, 93% were using temporary methods and only 7% using permanent methods. Among the contraceptives users oral contraceptive pill (OCP) was highest 56.1% followed by condom 15.8% and injectable 8.8%. Respondents got information about contraceptives mostly from family planning workers 50.9% followed by relatives 19.3%.Conclusion: Majority of the tribal couple of this study population were not using any contraceptives. Those couple were using contraceptives among them OCP was most common. Appropriate measure should be taken to increase the contraceptive use rate by tribal couples of Chattogram Hill Tracts.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 158-160